2003
DOI: 10.1096/fj.03-0187fje
|View full text |Cite
|
Sign up to set email alerts
|

Absence of heme oxygenase‐1 exacerbates atherosclerotic lesion formation and vascular remodeling

Abstract: To examine the role of heme oxygenase (HO)-1 in the pathophysiology of vascular diseases, we generated mice deficient in both HO-1 and apolipoprotein E (HO-1-/-apoE-/-). Despite similar total plasma cholesterol levels in response to hypercholesterolemia, HO-1-/-apoE-/- mice, in comparison with HO-1+/+apoE-/- mice, had an accelerated and more advanced atherosclerotic lesion formation. In addition to greater lipid accumulation, these advanced lesions from HO-1-/-apoE-/- mice contained macrophages and smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
177
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(187 citation statements)
references
References 53 publications
8
177
2
Order By: Relevance
“…Data from previous studies suggested that induction of HO-1 could inhibit cell growth [12,22,23] . VSMCs from HO-1-deficient mice display enhanced DNA synthesis and cell growth [24] . Conversely, over-expression of HO-1 by either transfection of the HO-1 gene or exogenous administration of a certain HO-1 inducer reduces excessive VSMC proliferation [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Data from previous studies suggested that induction of HO-1 could inhibit cell growth [12,22,23] . VSMCs from HO-1-deficient mice display enhanced DNA synthesis and cell growth [24] . Conversely, over-expression of HO-1 by either transfection of the HO-1 gene or exogenous administration of a certain HO-1 inducer reduces excessive VSMC proliferation [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The general atheroprotective actions of HO-1 are well documented (114,190). Recently, a more complete understanding of this process has implicated HO-1 expression within MP as an effector of atheroprotection (128).…”
Section: Ho-1 and Atheroprotective Macrophagesmentioning
confidence: 99%
“…11 The lack of HO-1 in HO-1 -/-/ApoE -/-double knock out mice dramatically worsens the process of atherogenesis. 12 It is generally assumed that Fe ++ , CO and/or biliverdin, the products of heme degradation, account for these anti-atherosclerotic effects even though the removal of heme by HO-1, and perhaps other effects of HO-1 may also be involved. Earlier studies from our laboratories showed that CO has anti-atherosclerotic effects by inhibition of VSMC proliferation.…”
Section: Introductionmentioning
confidence: 99%